2017
DOI: 10.1016/j.jembe.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Mexican origins for the Texas green turtle foraging aggregation: A cautionary tale of incomplete baselines and poor marker resolution

Abstract: The green turtle (Chelonia mydas) foraging aggregation along the Texas coast has increased dramatically in recent years, but the source populations for these turtles have not been adequately resolved. Previous mixed stock analysis (MSA) based on 490 base pair (bp) mitochondrial control region haplotypes suggested a large Florida contribution, but widespread sharing of common haplotypes among potential source populations and incomplete source population baseline data precluded precise assessment. To test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…6B) also appears consistent with existing data on the genetic structure of green turtles. For instance, the mitogenomics of stranded green turtles in Texas point toward origins from Mexico and Costa Rica, rather than Florida (Shamblin et al 2017) and our model's predictions of juvenile inputs to Texas from nesting beaches across Mexico and Costa Rica (but not Florida) are closely related to green turtle strandings (Supplementary material Appendix 1 Table A4). For the eastern Gulf of Mexico, genetic analyses of green turtles indicate inputs from populations in Mexico, Costa Rica and Florida, though proportions may vary over time or sub-regionally (Foley et al 2007, Naro-Maciel et al 2017, Shamblin et al 2018.…”
Section: Comparison Of Model Predictions To Observationsmentioning
confidence: 76%
“…6B) also appears consistent with existing data on the genetic structure of green turtles. For instance, the mitogenomics of stranded green turtles in Texas point toward origins from Mexico and Costa Rica, rather than Florida (Shamblin et al 2017) and our model's predictions of juvenile inputs to Texas from nesting beaches across Mexico and Costa Rica (but not Florida) are closely related to green turtle strandings (Supplementary material Appendix 1 Table A4). For the eastern Gulf of Mexico, genetic analyses of green turtles indicate inputs from populations in Mexico, Costa Rica and Florida, though proportions may vary over time or sub-regionally (Foley et al 2007, Naro-Maciel et al 2017, Shamblin et al 2018.…”
Section: Comparison Of Model Predictions To Observationsmentioning
confidence: 76%
“…The fact that FP tumors were first detected in green turtles at neritic foraging areas in southern Florida in 1937 (Hirama & Ehrhart 2007) and in the Hawaiian Islands in 1958(Balazs & Pooley 1991, but not in Texas until nearly half a century later, is compelling evidence and could provide clues regarding how the disease spreads to new areas. The Texas neritic foraging juvenile green turtle population is genetically distinct, indicating isolation of these western Gulf of Mexico juvenile green turtles (Shamblin et al 2017). Thus, the late appearance and increasing prevalence of FP in Texas green turtles could be due to novel incursion of the virus into an immunologically naive population.…”
Section: Discussionmentioning
confidence: 99%
“…This marker demonstrated that turtles nesting in Florida and Tamaulipas represented distinct populations. Subsequent MSA including the mtDNA SNP excluded Florida as a source of Texas foraging juveniles, and established the strong connectivity between this foraging aggregation and the newly proposed western Gulf of Mexico MU (Shamblin et al, 2017).…”
Section: Green Turtle Habitat Connectivity: Which Nesting Stocks Use mentioning
confidence: 98%
“…An MSA of juvenile green turtles in Texas foraging grounds suggested a large Florida rookery contribution based on the presence of these haplotypes at high frequencies (Anderson et al, 2013). Yet later analysis of the green turtle rookery at Rancho Nuevo, Tamaulipas, Mexico found CM-A1 and CM-A3 in the same frequencies as the central Florida MU, so the source of the majority of juveniles foraging in Texas remained unresolved using standard markers (Shamblin et al, 2015a(Shamblin et al, , 2017. However, mitogenomic sequencing of the CM-A1 females nesting in Rancho Nuevo and Florida identified a single diagnostic mtDNA SNP between the two rookeries.…”
Section: Green Turtle Habitat Connectivity: Which Nesting Stocks Use mentioning
confidence: 99%
See 1 more Smart Citation